Self-Presentation on Male Influencers in Surakarta on Instagram - Harsono, Aqila; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Influencers strive to develop a role both, and in accordance with their wishes. Social media sites have become increasingly crowded, including platforms such as Twitter, YouTube, Instagram, Facebook, and many others. The rise of these social media sites has had a significant impact on interactions between individuals. This is a way of motivating oneself and achieving the desired goals of Instagram influencers. Influencers have different motives when presenting themselves on Instagram, they will always prioritize details such as the setting of the place for photos, the costumes worn, the location of the place visited and many small things that are taken into account with the aim of getting a good impression in social media so that they can present themselves to other social users as desired. The main difference between influencers and non-influencer users is the influence that influencers have on others. Influencers have the power to influence others, whereas non-influencer users do not. This research aims to find out how the self-presentation of male influencers in Surakarta on Instagram. The research method used is qualitative with a descriptive approach and uses the theory of Dramaturgy by Erving Goffman. The sampling technique in this study was purposive sampling method. Data collected using in-depth interview techniques and document observation. The findings in this study using four informants show that the front stage emphasizes a positive lifestyle through its Instagram feed. While the backstage becomes himself in his normal life. The self-presentation of Surakarta city male influencers on Instagram aims to build personal branding, increase popularity, influence others, and earn income.